Propensity for risky choices despite lower cue reactivity in adolescent rats - Zeng, Sandford; McLaughlin, Elin F. B.; Ramesh, Aishwarya; Morrison, Sara E. (Frontiers in Behavioral Neuroscience, 2023)
Adolescence is a time of heightened risk-taking across species. Salient audiovisual cues associated with rewards are a common feature of gambling environments and have been connected to increased risky decision-making. We have previously shown that, in adult male rats, sign tracking -a behavioral measure of cue reactivity -predicts an individual's propensity for suboptimal risky choices in a rodent gambling task (rGT) with win-paired cues. However, adolescents perform less sign tracking than adult animals, suggesting that they are less cuereactive than adults in some circumstances. Therefore, we investigated the performance of adolescent male rats on the rGT with win cues and examined its relationship with their signtracking behavior. We found that adolescents make more risky choices and fewer optimal choices on the rGT compared with adults, evidence of the validity of the rGT as a model of adolescent gambling behavior. We also confirmed that adolescents perform less sign tracking than adults, and we found that, unlike in adults, adolescents' sign tracking was unrelated to their risk-taking in the rGT. This implies that adolescent risk-taking is less likely than that of adults to be driven by reward-related cues. Finally, we found that adults trained on the rGT as adolescents retained an adolescent-like propensity towards risky choices, suggesting that early exposure to a gambling environment may have a long-lasting impact on risk-taking behavior.